2015
DOI: 10.1016/j.pmatsci.2014.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Advantages and challenges of relaxor-PbTiO3 ferroelectric crystals for electroacoustic transducers – A review

Abstract: Relaxor-PbTiO3 (PT) based ferroelectric crystals with the perovskite structure have been investigated over the last few decades due to their ultrahigh piezoelectric coefficients (d33 > 1500 pC/N) and electromechanical coupling factors (k33 > 90%), far outperforming state-of-the-art ferroelectric polycrystalline Pb(Zr,Ti)O3 ceramics, and are at the forefront of advanced electroacoustic applications. In this review, the performance merits of relaxor-PT crystals in various electroacoustic devices are presented fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
362
1
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 699 publications
(371 citation statements)
references
References 454 publications
(479 reference statements)
2
362
1
6
Order By: Relevance
“…8. The temperature values recorded at depolarization were 100°C and 120°C for PMN-PT and PIN-PMNT-PT respectively, which are lower than the depolarization temperature values of 135°C and 191°C reported in literature [1]. This may be caused by a combination of high temperature and high electric field.…”
Section: System Working Conditionscontrasting
confidence: 67%
See 2 more Smart Citations
“…8. The temperature values recorded at depolarization were 100°C and 120°C for PMN-PT and PIN-PMNT-PT respectively, which are lower than the depolarization temperature values of 135°C and 191°C reported in literature [1]. This may be caused by a combination of high temperature and high electric field.…”
Section: System Working Conditionscontrasting
confidence: 67%
“…Relaxor-based ferroelectric single crystal piezoelectric materials ("piezocrystals") have gained huge interest in both academic research and industrial applications [1]. These materials exhibit extraordinary piezoelectric properties, making them suitable for a range of passive and active applications, including in high bandwidth and high sensitivity piezoelectric transducers [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Zhang et al and Sun et al [2][3][4] These properties are expected to be applied in high-quality piezoelectric devices, such as medical ultrasonic transducers, actuators, and sonars, as replacements for conventional PZT ceramics [4][5][6][7]. In the PZN-9PT crystal system, different from the normal ferroelectric (e.g., PT) [8] with a long coherent length of order, the random distribution of B-ions (here, B represents Zn, Nb, and Ti atoms) prevents the formation of the long-range ferroelectric order [8,9].…”
Section: Introductionmentioning
confidence: 97%
“…Recently, Zhang et al and Sun et al [2][3][4] demonstrated that the Pb(Zn1/3Nb2/3)0.91Ti0.09O3 (PZN-9PT) crystal exhibits an exceptionally large piezoelectric constant (d33 > 2000 pC/N) and electromechanical coupling factor in longitudinal bar mode (k33 > 92%). These properties are expected to be applied in high-quality piezoelectric devices, such as medical ultrasonic transducers, actuators, and sonars, as replacements for conventional PZT ceramics [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%